Electrochemical Determination of Sulphur‐containing Pharmaceuticals Using Boron‐doped Diamond Electrodes. Issue 7 (8th March 2016) - Abt, Bärbel; Hartmann, Andreas; Pasquarelli, Alberto; Strehle, Steffen; Mizaikoff, Boris; Kranz, Christine
Abstract: N‐acetylcysteine (NAC) and gentamicin sulfate (GS) are biologically and pharmaceutically relevant thiol‐containing compounds. NAC is well known for its antioxidant properties, whereas GS is an aminoglycoside that is used as a broadband antibiotic. Both pharmaceuticals play a significant role in the treatment of bacterial infections by suppressing the formation of biofilms. According to the European Pharmacopeia protocol, GS is analyzed by high performance liquid chromatography (HPLC) using gold electrodes for electrochemical detection. Here, we report the electrochemical detection of these compounds at NH2 ‐terminated boron‐doped diamond electrodes, which show significantly reduced electrode passivation, an issue commonly known for gold electrodes. Cyclic voltammetry experiments performed for a period of 70 minutes showed that the peak current decreased only by 1.6 %/7.4 % for the two peak currents recorded for GS, and 6.6 % for the oxidation peak of NAC, whereas at gold electrodes a decrease in peak current of 14.2 % was observed for GS, and of 64 %/30 % for the two peak currents of NAC. For their quantitative determination, differential pulse voltammetry was performed in a concentration range of 2–49 µg/mL of NAC with a limit of detection (LOD) of 1.527 µg/mL, and a limit of quantification (LOQ) of 3.624 µg/mL, respectively. The quantification of GS in a concentration range of 0.2–50 µg/mL resulted in a LOD of 1.714 µg/mL, and a LOQ of 6.420 µg/mL, respectively. Abstract :